Assessment of Knowledge, Attitude and Perception of Public on Climate Change and Typhoid in Sarawak - Jacqueline Ronna, Jacky (Universiti Malaysia Sarawak (UNIMAS), 2022)
Typhoid is a staph disease that spreads all through the body system and attacks a variety of tissues in the process. This disease is caused by Salmonella Typhi which can be related to food poisoning. The spreading of typhoid fever can be supported by climate change. This is because climate change in Sarawak has led to frequent and more severe flooding which can cause severe water contamination. Thus, this creates an environment suitable for the growth of S. Typhi and other waterborne pathogens. Hence, the purpose of the study is to conduct an assessment of knowledge, attitude and perception of public on climate change and typhoid in Sarawak. Questionnaires were used to examine the locals' knowledge about typhoid, climate change, and the connection between the two. The survey included 92 people, and the results suggested that the majority of them are aware of typhoid and climate change. The majority of participants, on the other hand, were unaware of the relationship between typhoid and climate change. As a result, there is no substantial relationship between local knowledge of typhoid and climate change and public perception of the typhoid-climate change association.